Accentuation of Intrinsic and Extrinsic Motivation Value for Employee Performance Effectiveness - Ni Made Nadia Suta Pradhani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The important role of employees or human resources in determining the success of a company is very necessary. Several studies reveal that there is a positive relationship between motivation and employee performance. Some of these studies say that the high working motivation of employees has a relationship that tends to achieve a fairly effective level of employee performance. This Writing Method Using descriptive, a method that aims to describe or provide an overview of the object under study. Motivation is one of the efforts in directing employees to work more optimally in accordance with the wishes of the company. Intrinsic motivation is motivation that comes from within the individual. This motivation results in the integrity of goals, both organizational goals and individual goals, both of which can be satisfied. The mission of employees to one another is a shared responsibility. This needs to be accentuated so that no employee feels that the workload is too heavy or there is no employee who feels he is being exaggerated among other employees. Awards given by the company can trigger individual self-reward, meaning that employees who get more awards from the company can motivate them to work more effectively. Employees who have high motivation to occupy a higher position in the organization are likely to be able to increase work productivity in order to achieve organizational goals and vice versa. By understanding the role played in motivation, a manager will be able to increase the work productivity of his subordinates and can further improve their performance.